2004
DOI: 10.1038/sj.leu.2403258
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immune reconstitution after subcutaneous alemtuzumab (anti-CD52 monoclonal antibody, CAMPATH-1H) treatment as first-line therapy for B-cell chronic lymphocytic leukaemia

Abstract: Little information is available on long-term immune reconstitution after therapy with alemtuzumab in B-CLL patients. We present long-term follow-up data for blood lymphocyte subsets analysed by flow cytometry in previously untreated B-CLL patients who received alemtuzumab subcutaneously as firstline therapy. All lymphoid subsets were significantly (Po0.001) and profoundly reduced; the median end-of-treatment counts þ and CD8 þ levels in blood had reached 4100 cells/ll in 450% of the patients at 4 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 22 publications
3
75
1
Order By: Relevance
“…30 Transient proliferation of CD52-negative T cells after cross-linking, and subsequent downregulation of CD52 by alemtuzumab has been observed in patients treated for chronic lymphocytic leukemia. 31 Our data are the first to describe long-term persistence of substantial CD52-negative T-cell populations after alemtuzumab-mediated TCD transplantation. They also indicate that CD52 can be used as a marker to track the re-population of the T-cell repertoire with exogenously administered CD52-positive T cells of donor origin.…”
Section: Resultsmentioning
confidence: 59%
“…30 Transient proliferation of CD52-negative T cells after cross-linking, and subsequent downregulation of CD52 by alemtuzumab has been observed in patients treated for chronic lymphocytic leukemia. 31 Our data are the first to describe long-term persistence of substantial CD52-negative T-cell populations after alemtuzumab-mediated TCD transplantation. They also indicate that CD52 can be used as a marker to track the re-population of the T-cell repertoire with exogenously administered CD52-positive T cells of donor origin.…”
Section: Resultsmentioning
confidence: 59%
“…The study showed that even lower cumulative doses of alemtuzumab could result in a sharp decrease in cell numbers for an extended period of time, although the cumulative dose level was not significantly associated with the extent or duration of lymphocyte depletion. There was, however, a trend toward lower levels of CD4 + and CD8 + T cells at the end of therapy in patients who received greater than median cumulative doses of alemtuzumab, although the actual bloodstream concentrations of alemtuzumab were not measured [34]. Interestingly, no late-occurring opportunistic infections or major infections were reported during unmaintained, long-term follow-up; this may partially be explained by the patients' treatment-naive status prior to alemtuzumab therapy.…”
Section: Effect Of Alemtuzumab On Immune Cellsmentioning
confidence: 92%
“…An array of immune cell populations was examined by flow cytometry at baseline and through 18 months following first-line alemtuzumab treatment [34]. CD4 + and CD8 + T cells, CD3 − /56 + NK cells, CD3 + /56 + NK T cells, and CD19 + /5 − B cells were all profoundly decreased to <25% baseline through 9 months after treatment.…”
Section: Effect Of Alemtuzumab On Immune Cellsmentioning
confidence: 99%
“…The frequent and sometimes severe infusional reactions can be significantly reduced by administering the drug subcutaneously instead of intravenously [14].…”
Section: Alemtuzumabmentioning
confidence: 99%